Microshear Bond Strength of Bioactive Materials to Dentin and Resin Composite - Ahmed, Basma; Hamama, Hamdi H.; Mahmoud, Salah Hasab (European Journal of Dentistry, 2022)
Objectives The aim of this study was to comparatively evaluate microshear bond strength (μSBS) of bioactive ionic resin composite and resin-modified glass ionomer liner (RMGI) to dentin and resin composite.Materials and Methods The enamel of 11 posterior molar teeth was removed to expose dentin and then placed in acrylic blocks. Each specimen received three microcylindrical Tygon tubes filled with bioactive ionic resin composite (Activa Bioactive base/liner (Pulpdent, MA, USA)), RMGI (Riva light cure SDI LTD, Bayswater, Australia), and resin composite (Filtek Z350xt, MN, USA). Composite discs (n = 11) were fabricated from nanofilled resin composite (Filtek Z350xt) and then fixed in acrylic blocks. Each specimen received two microcylindrical Tygon tubes filled with Activa Bioactive base/liner and Riva RMGI. All specimens were mounted individually to universal testing machine for μSBS test. Failure modes were analyzed using stereomicroscope and scanning electron microscope.Results Filtek Z350xt nanofilled resin composite showed the highest μSBS values. No statistical significant difference was found between Activa Bioactive and Riva RMGI (p > 0.05).Conclusion Bioactive ionic resin composite liner exhibited similar bond strength as RMGI to dentin and resin composite.
Keywords: bioactive materials; resin-modified glass ionomer; microshear; glass ionomer